2014
DOI: 10.1186/1471-2180-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas pyocyanin stimulates IL-8 expression through MAPK and NF-κB pathways in differentiated U937 cells

Abstract: BackgroundPyocyanin (PCN), an extracellular product of Pseudomonas aeruginosa and a blue redox active secondary metabolite, plays an important role in invasive pulmonary infection. However, the detailed inflammatory response triggered by PCN infection in inflammatory cells (particularly macrophages), if present, remains to be clarified. To investigate the effects of PCN on macrophages, the ability of PCN to induce inflammation reaction and the signaling pathway for IL-8 release in PCN-induced differentiated U9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…In megakaryocytes, the p38 MAPK pathway has been shown to be essential for megakaryocyte rupture‐dependent thrombopoiesis, which increases platelet production . In addition, activation of the p38 MAPK pathway results in further activation of NF‐κB and release of anti‐inflammatory cytokines to recruit neutrophils at the site of infection . Our finding of PAO1‐induced p38 activation in Mo7e cells suggests that megakaryocytes undergoes cytotoxicity by modulating signaling pathways in a similar manner to that of other immune effector cells reported so far.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In megakaryocytes, the p38 MAPK pathway has been shown to be essential for megakaryocyte rupture‐dependent thrombopoiesis, which increases platelet production . In addition, activation of the p38 MAPK pathway results in further activation of NF‐κB and release of anti‐inflammatory cytokines to recruit neutrophils at the site of infection . Our finding of PAO1‐induced p38 activation in Mo7e cells suggests that megakaryocytes undergoes cytotoxicity by modulating signaling pathways in a similar manner to that of other immune effector cells reported so far.…”
Section: Discussionsupporting
confidence: 78%
“…Innate cells respond to bacterial infection and modulate signaling mechanisms through recognition of bacterial components by their receptors. In most of the earlier studies, surface antigens (i.e., LPS and flagellin) and secretary virulence factors (i.e., pyocyanin and alkaline protease) of P. aeruginosa were found to activate the p38 pathway, resulting in secretion of pro‐inflammatory cytokine such as TNF‐α, IL‐6 and IL‐8 . Our observation that PAO1 lysate induces p38 activation may indicate recognition of any of these secretary virulence factors by Mo7e cells; this possibility requires further study.…”
Section: Discussionmentioning
confidence: 71%
“…However, with increase in wound healing time point, loss of viability of P.aeruginosa, and inactivation of its virulent factors possibly led to significant down regulation of NF-kB and inflammatory cytokines. It has been shown that virulent factors secreted by P.aeruginosa such as LPS, phospholipase, proteolytic enzymes and pyocyanin induce damage to fibroblast, endothelial cells in the wound milieu and delay the wound healing [4][5][6]31) . Also, a prolonged inflammatory phase induced by infection, causes increased levels of proteases which destroy components of the extracellular matrix and damage the growth factors 31) .…”
Section: Original Articlesmentioning
confidence: 99%
“…Management of infections caused by P. aeruginosa is difficult due to the rapid emergence of multi-antibiotic resistant strains. Further, the toxins and cell components of these bacteria such as lipopolysaccharide (LPS) can induce overproduction of local proinflammatory mediators, casue cell death [3][4][5][6][7][8][9] . Proteases produced by these bacteria also degrade host matrix proteins, thereby impairing host tissue integrity [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Pyocyanin is a blue phenazine redox active secondary metabolite of PA causes adverse invasive pulmonary infection by inhibiting the ciliary function, epidermal cell growth and prostacyclin release [33]. In the presence of 50 µg/ml of EA extract, 19.3±1.2% of pyocyanin production has inhibited.…”
Section: Inhibition Of Qs-regulated Pigment Productionmentioning
confidence: 99%